Incidence of BRCA1/2 germ line alterations in a high risk cohort participating in a phase II chemoprevention trial - Klemp, J; Brady, D; Frank, T.S; Kimler, B.F; Fabian, C.J (European journal of cancer (1990), 2000)
It is unknown what proportion of women at high risk for breast cancer, entering phase II chemoprevention trials, have BRCA1/2 alterations, and whether their initial biomarker patterns or response to preventive interventions will differ between carriers and non-carriers. As part of a 6-month phase II chemoprevention trial of diflouromethlyornithine (DFMO), high-risk subjects (family history, prior precancerous breast disease or prior breast cancer), who had random peri-areolar fine needle evidence of epithelial hyperplasia with or without atypia, were offered genetic counselling and testing at the completion of their study participation. 97% of the 119 women eligible for testing underwent BRCA1/2 gene sequencing, 3 declined. 26 (22%) of the 116 women had an alteration in BRCA1/2. Known deleterious mutations were present in 3 (3%), uncertain significance mutations in 19 (16%), and probable polymorphisms in 6 (5%). There does not appear to be a difference in initial biomarker distribution between participants with and without germ line alterations.